2018
DOI: 10.1111/gcb.14381
|View full text |Cite
|
Sign up to set email alerts
|

Closing the global ozone yield gap: Quantification and cobenefits for multistress tolerance

Abstract: Increasing both crop productivity and the tolerance of crops to abiotic and biotic stresses is a major challenge for global food security in our rapidly changing climate. For the first time, we show how the spatial variation and severity of tropospheric ozone effects on yield compare with effects of other stresses on a global scale, and discuss mitigating actions against the negative effects of ozone. We show that the sensitivity to ozone declines in the order soybean > wheat > maize > rice, with genotypic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(177 citation statements)
references
References 143 publications
(268 reference statements)
6
142
3
Order By: Relevance
“…In the near future, this could include selection of existing cultivars that may be more resistant to the local pollution climate, but in the longer term selective breeding could be used to increase the prevalence of traits or genes associated with ozone resistance. An ideotype for an ozone‐tolerant crop has been suggested, which includes target traits of increased water‐use efficiency, low stomatal conductance, high antioxidant capacity and balanced redox homeostasis and programmed cell‐death pathways, as ozone sensitivity can be a consequence of some traits identified when developing high‐yielding varieties (Mills, Sharps, Simpson, Pleijel, Frei, et al, ). Studies have identified some genetic loci associated with ozone resistance and/or susceptibility in wheat and rice (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the near future, this could include selection of existing cultivars that may be more resistant to the local pollution climate, but in the longer term selective breeding could be used to increase the prevalence of traits or genes associated with ozone resistance. An ideotype for an ozone‐tolerant crop has been suggested, which includes target traits of increased water‐use efficiency, low stomatal conductance, high antioxidant capacity and balanced redox homeostasis and programmed cell‐death pathways, as ozone sensitivity can be a consequence of some traits identified when developing high‐yielding varieties (Mills, Sharps, Simpson, Pleijel, Frei, et al, ). Studies have identified some genetic loci associated with ozone resistance and/or susceptibility in wheat and rice (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of compiled data sets from many experiments has shown a wide range in ozone sensitivity between different crops, based on ozone concentration (Mills et al, ; Mills & Harmens, ; Mills, Sharps, Simpson, Pleijel, Broberg, et al, ). Model‐based studies using dose‐response functions from such data sets have indicated potential crop yield reductions due to ozone across wide regions of the world (Avnery, Mauzerall, Liu, & Horowitz, ; Mills, Pleijel, et al, ; Mills, Sharps, Simpson, Pleijel, Broberg, et al, ; Mills, Sharps, Simpson, Pleijel, Frei, et al, ; Van Dingenen et al, ). Experimental investigations have shown impacts of ambient ozone concentrations on a wide range of crop species in Europe and the USA by comparing responses of plants in filtered air to those in non‐filtered air (De Temmerman, Legrand, & Vandermeiren, ; Marzuoli, Finco, Chiesa, & Gerosa, ; Pleijel, Broberg, Uddling, & Mills, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much of the ozone data are from the NH mid-high latitudes of the developed world (20 to 60° N), with very limited data available for rapidly developing countries of Africa, South America, and parts of SAS/SEA. TOAR has strong representation in areas of NAM and EUR predicted to have high ozone impacts on crops (Avnery et al, 2011;Van Dingenen et al, 2009;Mills et al, submitted) and biodiversity (Fuhrer et al, 2016) such as central states of the USA and Mediterranean areas. However, other areas predicted from modelling to have high impacts of ozone on vegetation such as northern areas of India and the northern plains of China (e.g.…”
Section: Spatial Representativeness Of Analysismentioning
confidence: 99%
“…Avnery et al, 2011;Van Dingenen et al, 2009) or stomatal ozone uptake (e.g. Mills et al, 2018;Mills et al, submitted). For perennial vegetation, there is good representation of data in mid-latitudes of the Northern Hemisphere where grassland and forested areas provide grazing, harvestable biomass and other ecosystem services.…”
Section: Spatial Representativeness Of Analysismentioning
confidence: 99%
“…Tropospheric ozone is an important greenhouse gas contributing to global warming [1,2] and also a main pollutant harmful to human health and crop productivity [3,4]. A significant decrease of ozone concentrations has been observed in the eastern United States and parts of Europe due to precursor emission controls [2,5,6].…”
Section: Introductionmentioning
confidence: 99%